A Feasibility study on HerbyGel an Anti-Toothache Herbal Toothpaste - Abad, George R. II; Cerrero, Geraldine T.; Ty, Laura Blossom E.; Villanueva, Farah C. (College of Engineering, 1999)
HerbyGel is an anti-toothache herbal toothpaste made of all natural ingredients with herbally modified coconut oil as its active ingredient. This was invented by retired Chemical Engineer Benjamin Samson. It can be used as a regular or special purpose toothpaste, but will be marketed as regular toothpaste with special features competitive with leading brands. The product will be sold in three different sizes: 100-g, 50-g tubes and 10-g sachets.Based on the market study conducted, the market for toothpaste has remained stable as evidenced by the increasing demand for it. And with annual planned sales of 448 million grams to 486 million grams of toothpaste, the project will maintain a market share of 1% of the toothpaste industry. The project will be targeting children with ages ranging from 2 to 12 years residing in the National Capital Region, Bulacan, Cavite, Laguna and Rizal. The product will be distributed using one level method of distribution with price ranging from P80, P45, and P10 for the 100g, 50g tube and 10g sachet respectively. Rigorous promotional and advertising campaign will be employed with an estimated budget of P6,208,000 for the first year and budget decreases for the succeeding years. HerbyGel is consists of 80% refined coconut oil, 15% chemicals and 5% herbs. The product will be packaged using plastic laminated tubes and sachets. The major processes involved in the manufacture of toothpaste include preparation of ingredients, heating of refined coconut oil, cooling of heated coconut oil with herbs, mixing of cooled coconut oil with herbs and chemicals, tube sachet filling and sealing, and packaging. Production processes are machine-intensive except for packaging that is done manually based on the technical study made. One-month inventory of finished goods will be maintained to absorb shocks of fluctuating demand. Based on estimated processing times, 15 batches of production are necessary to meet the daily demand with full capacity of 2,550,000 grams per day. Thus one shift of production would be implemented but packaging would require overtime while maintaining constant workforce for the next 5 years. The project involve 12 workers directly involved in production and 17 members of support staff. The plant will be located at Kaybiga, Caloocan City with area of 2500 square meter just enough for the 2441.75 square meter space requirement of the project. Total project cost which consists of cost investment, manufacturing, operating expenses, administrative expenses and 10%contingency amounted to P137,431,857.40 For the next four years, operating cost, will amount to P106,094,987. To determine if the six-month operation cost is adequate to start the project, a total of P88,624,308 is computed. In establishing the organization of the project, the corporation was chosen to be the most effective. The general Manager would head the organization which will consist of six departments, Production, Marketing, Sales, Finance, Purchasing, Research and Development and Human and Resource Development. The company would employ 25 administrative and 29 labor personnel. Manpower would be given 13th month pay, SSS, Medicare and 10% annual increase to their basic salaries and wages.